Non pharmacological therapy for anxiety of a child with cancer During chemotherapy : Literatur Review - Totok Wahyudi; Endrat Kartiko Utomo; Annisa Yuli Kartikasari; Dessy Nourma Siska Savitri (LPPM Universitas Duta Bangsa Surakarta, 2022)
Anxiety in cancer patients is a psychological disorder caused because the patient faces uncertainty, worry about the effects of cancer treatment, and fear of the development of cancer resulting in death. A child's response to anxiety is varied, influenced by various factors such as the child's developmental age, gender, length of treatment, and previous experiences of pain. Non-pharmacological therapy is a treatment therapy without the use of drugs. Non-pharmacological therapy has significant benefits for reducing a wide range of side effects of chemotherapy including, anemia, thrombocytopenia, leucopenia, nausea, vomiting, alopecia, stomatitis, reactionallergy, neurotoxic, and extravasation. The main focus of this review literature is nonpharmacological therapy for anxiety of children with cancer During chemotherapy. To optimize this interpretation, researchers used the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guide. From the Google Scholar database found a number of journals a total of 20 results, PubMed found 10, Science Direct 22. Then, the literature is screened whether it is in accordance with the inclusion criteria that have been set in this study. At the final stage only five journals were used for the synthesis process. All five articles are of such good quality that no one is eliminated from the critical appraisal process. Non-pharmacological therapies have significant benefits for reducing various side effects of chemotherapy including anemia, thrombocytopenia, leukopenia, nausea, vomiting, alopecia, stomatitis, allergic reactions, neurotoxicity, and extravasation. Various interventions such as music, autogenic exercises, mindfullnes programs, virtual reality, guided imagery and progressive muscle exercises are considered necessary to be applied in Indonesia.